2019
DOI: 10.1158/1078-0432.ccr-18-3932
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-enhanced MRI Is Feasible, Repeatable, and Detects Radiotherapy-induced Change in Hypoxia in Xenograft Models and in Patients with Non–small Cell Lung Cancer

Abstract: Purpose: Hypoxia is associated with poor prognosis and is predictive of poor response to cancer treatments, including radiotherapy. Developing noninvasive biomarkers that both detect hypoxia prior to treatment and track change in tumor hypoxia following treatment is required urgently. Experimental Design: We evaluated the ability of oxygenenhanced MRI (OE-MRI) to map and quantify therapyinduced changes in tumor hypoxia by measuring oxygenrefractory signals in perfused tissue (perfused Oxy-R). Clinical first-in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 47 publications
1
73
0
Order By: Relevance
“…Ohno et al did incidentally report on a lung tumor and stated that there was minimal BOLD response to oxygen breathing challenge compared to the surrounding lung . Small studies of oxygen‐sensitive MRI have been reported for human lung tumors, which indicated detectable BOLD changes and recently R 1 changes with respect to an oxygen gas breathing challenge. Most studies of human lung have focused on chronic obstructive pulmonary disorder and asthma, thereby examining the lung itself .…”
Section: Discussionmentioning
confidence: 99%
“…Ohno et al did incidentally report on a lung tumor and stated that there was minimal BOLD response to oxygen breathing challenge compared to the surrounding lung . Small studies of oxygen‐sensitive MRI have been reported for human lung tumors, which indicated detectable BOLD changes and recently R 1 changes with respect to an oxygen gas breathing challenge. Most studies of human lung have focused on chronic obstructive pulmonary disorder and asthma, thereby examining the lung itself .…”
Section: Discussionmentioning
confidence: 99%
“…53 Preclinical and clinical studies have demonstrated that the volume of oxygenrefractory voxels can be used to map and quantify hypoxic fractions across a range of tumour types. [54][55][56][57] OE-MRI revealed extensive tumour subregions that were refractory to oxygeninduced signal intensity changes in a syngeneic rat rhabdomyosarcoma model, again consistent with the presence of hypoxia. 49,50 Preliminary OE-MRI investigations in RH41 rhabdomyosarcoma xenografts also suggest a strong hypoxia signature in this tumour type ( Fig.…”
Section: Hypoxia Imagingmentioning
confidence: 55%
“…MRI is used routinely in healthcare, and both IS-MRI and OE-MRI have been implemented on standard clinical scanners and used to assess tumour hypoxia in adult patients. 55,57,58 Whilst the application of MRI protocols in children can be challenging due to the logistical challenges involved, such as having to sedate/ anaesthetise younger patients to undergo the exam, rapid mapping of tumour hypoxia with IS-MRI and OE-MRI, which both rely on endogenous contrast mechanisms, is totally non-invasive and relatively straightforward to incorporate into existing clinical imaging protocols. We predict that within the next 5-10 years, this is likely to enhance imaging-embedded investigations associated with clinical interventions that may ultimately improve the outcome for paediatric patients.…”
Section: Hypoxia Imagingmentioning
confidence: 99%
“…Lessons learned from clinical trials of HAPs such as Evofosamide have clearly identified the importance of integrating hypoxia imaging with hypoxia targeting strategies [39] , [40] , [41] , [42] , [43] . Imaging of tumor targeted NPs delivering cDNA of a hypoxia driven prodrug enzyme in combination with hypoxia imaging using PET [44] or MRI [45] may provide translational approaches for hypoxia theranostics.…”
Section: Discussionmentioning
confidence: 99%